Case Report: VV-ECMO as a bridge to recovery from ACE inhibitor induced post-obstructive negative pressure pulmonary edema - Smirnova, Darja; Steina, Eva; Klibus, Mara; Prozorovskis, Edgars; Strike, Eva; Sabelnikovs, Olegs (Frontiers in Medicine, 2025)
The indications for extracorporeal membrane oxygenation (ECMO) are becoming increasingly widespread nowadays. This case report describes the unique presentation of an adult patient with a combination of two rare complications: life-threatening angioedema caused by angiotensin-converting enzyme inhibitors (ACEi) and subsequent post-obstructive negative pressure pulmonary edema (NPPE). In this case, worsening angioedema that was unresponsive to medication led to severe airway obstruction and near-fatal acute respiratory syndrome due to NPPE. The worsening clinical course required a multidisciplinary approach and immediate initiation of extracorporeal membrane oxygenation (VV-ECMO). The literature reports that most NPPE cases resolve with oxygenation. However, in our case, the NPPE was refractory to mechanical ventilatory support, and we had to initiate VV-ECMO to prevent the patient from going into cardiac arrest due to severe hypoxia. This case underscores the critical role of VV-ECMO as a bridge to recovery from severe NPPE. It also highlights the need to raise clinicians’ awareness of the potential life-threatening side effects of the commonly used antihypertensive drug perindopril.